The role of procurement procedures in environmental management: A case study of classified hotels in Mombasa County, Kenya - Akinyi Odeny, Jane; Maingi, Shem; Kurauka, Joseph (Hotel and Tourism Management, 2020)
This paper sought to examine the role of procurement procedures on environmental management. It adopted a cross-sectional descriptive research design that involved collecting and analyzing data of observations about the role of procurement practices on environmental management from a representative sample of managerial staff of classified hotels in Mombasa County, Kenya. The data collected was primary data. It was collected from staff in 69 hotels in Mombasa County, Kenya. The research used stratified random sampling technique where the employees were categorised into seven strata of general/assistant managers, food and beverage managers, executive chef, procurement officers, maintenance managers, receiving managers and housekeepers. From each of the stratum, a random sample was identified. The study employed Yamane’s formula to determine the sample size. The study determined that procurement procedures influenced environmental management. The study also determined that some of the procurement procedures were perceived to have a greater influence than others. The most influential procurement procedure on environmental management is tendering adverts that attract suppliers offering environmentally friendly products, while the least influential is assessing the impact of suppliers on the environment prior to purchasing.